POEM-based SofLP’s Inculcation: A Way of Improving EFL Students’ Pragmatic Competence - Telaumbanua, Yohannes (Universitas Negeri Makassar, 2020)
The facts disclosed that some Indonesian ED students have difficulty disassembling the SIM in a practical sense. The scopes, focusing on merely learning factual knowledge of linguistic pragmatics and plus discussing the Western-based cases in point provided which are contrary to the Indonesian ED students’ real-world life social contexts, are the major quandaries of the students’ difficulties. The researcher, therefore, proposed such a title to practically bridge the students’ critical quandaries in interpreting the SIM. This was a qualitative method whose complete participation, field-notes, interviews, and iterative model and the 1984 Miles and Huberman Interactive model were the techniques of collecting and analysing the data respectively. The principal results practically signified that the poem-based SofLP’s inculcation better improve the Indonesian ED students’ pragmatic competence, HOTs (cognitive process and knowledge domains), linguistic intelligence and language skills. Besides, through poem, the pragmatic language teacher is encouraged to exploit the instructional strategies to establish and develop the students’ space practice, retrieval practice, elaboration, and collaboration. In conclusion, even though it seems weird, the poem or other literary works and digital media can critically serve as the learning media assisting the students acquire the SofLP.